Positron and infrared spectroscopy detection of oxidation rate and service properties of tool materials - Nesterenko V. P.; Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Merkulov V. I.; Kondratyuk A. A.; Surkov A. S. (2001, 2001)
The positron and infrared spectroscopy is used to study the correlation between the mechanism and intensity of oxidation of hard alloy tool materials and their wear resistance. It is shown that the interaction of oxygen with the hard alloy components considerably affects the subsequent adsorption activity of polyoxides. The qualitative and quantitative parameters of distributions of carbonyl, carbonate and hydroxyl groups on the surface and subsurface oxide layers on a cutting tool strongly affect its wear resistance and simultaneously provide an essential information for estimating and forecasting its service properties.